2013
DOI: 10.3347/kjp.2013.51.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Echinostoma revolutum: Freshwater Snails as the Second Intermediate Hosts in Chiang Mai, Thailand

Abstract: The occurrence of 37-collar spined echinostome metacercariae in freshwater snails was investigated in 6 districts of Chiang Mai Province, Thailand, from October 2011 to April 2012. A total of 2,914 snails that belong to 12 species were examined, and 7 snail species (Clea helena, Eyriesia eyriesi, Bithynia funiculata, Bithynia siamensis siamensis, Filopaludina doliaris, Filopaludina sumatrensis polygramma, and Filopaludina martensi martensi) were found infected with echinostome metacercariae. The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
7
29
1
Order By: Relevance
“…Regarding the snail hosts, B. s. siamensis were found to be infected with monostome, gymnocephalus and virgulate cercariae. Previous reports found the same type of cercariae in this snail from Chiang Mai province [ 32 , 44 ]. The cercariae fauna in our study area was quite diverse with 7 morphotypes, some of which might represent more trematode species and besides the fish-born zoonotic trematode types other species are potentially zoonotic, such as the echinostomes [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding the snail hosts, B. s. siamensis were found to be infected with monostome, gymnocephalus and virgulate cercariae. Previous reports found the same type of cercariae in this snail from Chiang Mai province [ 32 , 44 ]. The cercariae fauna in our study area was quite diverse with 7 morphotypes, some of which might represent more trematode species and besides the fish-born zoonotic trematode types other species are potentially zoonotic, such as the echinostomes [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 78%
“…Previous reports found the same type of cercariae in this snail from Chiang Mai province [ 32 , 44 ]. The cercariae fauna in our study area was quite diverse with 7 morphotypes, some of which might represent more trematode species and besides the fish-born zoonotic trematode types other species are potentially zoonotic, such as the echinostomes [ 44 , 45 ]. Echinostome cercariae were discovered in viviparid snail ( F. s. polygramma ), whereas several studies have reported identifying it in planorbid, lymnaeid and thiarid snails [ 38 , 46 , 47 ], and they were reported to be present as the cercarial stage of the trematodes in family Echinostomatidae [ 48 ].…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, the size of the worms was smaller compared with the results of the above-mentioned report [ 11 ]. Moreover, our study showed different size of adult worms in different host models which was different from a previous report which showed the same size of E. revolutum adults recovered from different hosts, i.e., hamsters and domestic chicks [ 14 ].…”
Section: Discussioncontrasting
confidence: 99%
“…One of the important modes of transmission of echinostomiasis is eating raw freshwater snails. Although raw snail consumption is uncommon in the study area, human echinostomisasis is a public health concern in Southeast Asia (Chantima et al, 2013). More research must therefore be done with regards to the wide-spread species introduction because of the unknown impacts to the ecosystems and the potential consequences to public health.…”
Section: Interactions Between Snail Speciesmentioning
confidence: 99%
“…martensi snails as a biological control agent for Bithynia snails requires careful considerations as F.m. martensi snails have been found to be infected with the metacercariae of the intestinal fluke, Echinostoma spp., in north Thailand (Chantima et al, 2013), as well as in the sampling sites of this study (Wang, unpublished data). One of the important modes of transmission of echinostomiasis is eating raw freshwater snails.…”
Section: Interactions Between Snail Speciesmentioning
confidence: 99%